Awareness of Tadika’s (Kindergarten) Children towards Healthy Lifestyle in Kuala Terengganu, Malaysia - Ahmed G. Alattraqchi, Muhamad Arif Fahmi Bin Abu Bakar, Farah Afiqah Binti Abu Bakar Mohamad, Anis Izzati Binti Abdul Kadir, Nur Amalina Binti Mohd Yahya, Nur Azmina Binti Juhari, Salwani Ismail, Nor Iza A Rahman, Mainul Haque (Journal of Applied Pharmaceutical Science, 2014)
Health is a common need for every human being. Six point six (6.6) million children under the age of five died in 2012. These child deaths are due to conditions that could be prevented or treated with access to simple and cheap interventions. Leading causes of death in under-five children are pneumonia, preterm birth complications, birth asphyxia, diarrhoea and malaria. School is the primary place of awareness and actually education enlighten people to practice safe-lifestyle. Therefore, World Health Organisation (WHO) launched in 1995 a Global School Health Initiative to incorporate health education in schools for children. Therefore, the current study was conducted with objective is to identify children’s awareness towards healthy lifestyle in the aspects of eating behavior, personal hygiene and physical activities. The specific objectives are: to evaluate the awareness level of children towards healthy lifestyle; to identify the attitude level of children in practicing healthy lifestyle; to document and correlate the level of awareness and attitude of children in practicing healthy lifestyle. Current study is a cross sectional study and conducted among children of a kindergarten named Tadika Nurul Iman As-Siddiq, Malaysia. Present study population was 60 children. All the students are Malay in race and religion is Islam. Sixty-eight percent of kids are familiar with the types of food to stay healthy. They also agreed (78%) that knowledge of healthy food is important. Proper authority should take initiative to conduct prospective research. Therefore necessary measures and interventions can be initiative in very early to have healthier Malaysian national.
Keywords: Awareness,Children,Kindergarten,Malaysia.